THE ROLE OF LOCAL ULAMA IN BUILDING PEACE SOCIAL IN POST-CONFLICT AREAS - Najmuddin, Muhammad; Rakhmat, Rakhmat (State Islamic University of Datokarama Palu, 2025)
This article discusses the role of local clerics in building social peace in Sigi Regency, an area that is still experiencing post-conflict communal tensions. Conflicts that occurred in the past leave trauma and resentment, which are intergenerational inheritance​ in a hereditary way. In this situation, the ulama play a role as agents actualizing peace, moderate Islamic values through moderate and contextual da'wah. Research This approach uses qualitative methods with design studies, case studies, which rely on primary data from in-depth interviews, participatory observation, and field documentation. Research results show that scholars carry out three leading roles: as social mediators, preachers of peace, and guardians of the collective narrative. The da'wah strategy used participatory, dialogical, and cultural approaches, which proved effective in building social cohesion and care in the community. However, scholars also face various challenges, such as resistance from extreme groups, limitations on source power, and unresolved social trauma that has not fully recovered. Research confirms that the role of scholars in social reconciliation is vital, and the Wasathiyah da'wah strategy has the potential to be a big instrument for social transformation in post-conflict societies. This study recommends strengthening support, structural, and development synergy across actors to strengthen efforts for peace from the root.